Curable resin composition, cured product, diffractive optical element, multi-layer diffractive optical element

The curable resin composition with core-shell ITO particles and a dispersant stabilizes dispersion, ensuring high transmittance and refractive index stability across visible to short-wave infrared wavelengths, addressing the limitations of existing compositions.

JP7616921B2Active Publication Date: 2025-01-17FUJIFILM CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021043194
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-17
Publication Date
2025-01-17
Estimated Expiration
2041-03-17

AI Technical Summary

Technical Problem

Existing curable resin compositions struggle to maintain high transmittance and wavelength dependence of refractive index across the visible light to short-wave infrared wavelength range, particularly when incorporating ITO particles, and suffer from dispersion stability issues over time.

Method used

A curable resin composition featuring core-shell structured ITO particles with specific tin concentration profiles and a dispersant, which includes a monofunctional or multifunctional (meth)acrylate compound, to stabilize the dispersion and enhance transmittance.

Benefits of technology

The composition achieves high transmittance and maintains refractive index wavelength dependence across the visible to short-wave infrared range, suitable for diffractive optical elements and multilayer diffractive optical elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007616921000013
    Figure 0007616921000013
  • Figure 0007616921000014
    Figure 0007616921000014
  • Figure 0007616921000001
    Figure 0007616921000001
Patent Text Reader

Abstract

To provide a curable resin composition containing ITO particles from which a cured product can exhibit high transmittance while keeping wave dependency at a desired refractive index from visible light to an infrared wavelength region at a short wavelength can be obtained, and a cured product using the same, a diffractive optical element and a multilayer type diffractive optical element.SOLUTION: There are provided a curable resin composition which has a core-shell type structure, where the core part contains particles composed of an indium tin oxide, a mono- or polyfunctional (meth)acrylate compound, and a dispersing agent, a cured product using the same, a diffractive optical element and a multilayer type diffractive optical element.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a curable resin composition. The present invention also relates to a cured product, a diffractive optical element, and a multi-layer diffractive optical element obtained by using the curable resin composition. [Background technology]

[0002] By using a diffractive optical element, it is possible to obtain a lens in which the focal length is shorter for longer wavelengths and in which chromatic aberration is expressed in the opposite manner to conventional refractive lenses. Unlike refractive lenses that require multiple lenses to correct chromatic aberration, chromatic aberration can be corrected by changing the period of the diffractive structure of the lens, so by using a diffractive optical element, it is possible to design a more compact, high-performance lens unit.

[0003] In a multi-layer diffractive optical element having a configuration in which diffractive optical elements formed from two different materials are in contact with each other at their grating surfaces, one diffractive optical element is formed from a material with a relatively high refractive index and a high Abbe number, and the other diffractive optical element is formed from a material with a relatively low refractive index and a low Abbe number, thereby suppressing the occurrence of flare within the lens and making full use of the chromatic aberration reduction effect. In this case, if the two diffractive optical elements have optical characteristics in which the difference in refractive index between them is greater at longer wavelengths, the chromatic aberration reduction effect can be obtained over a wide wavelength range.

[0004] In recent years, in order to obtain the above-mentioned chromatic aberration reduction effect in a wide wavelength range, it has been proposed to add ITO (indium tin oxide) particles to a low Abbe number diffractive optical element in a multi-layer diffractive optical element. For example, Patent Document 1 discloses a curable resin composition for producing a diffractive optical element, which is characterized in that ITO particles are dispersed in a resin containing a photopolymerization initiator, a dispersant, and two or more acrylic groups, methacrylic groups, or vinyl groups, or a mixture of these unsaturated ethylene groups. Patent Document 2 describes a resin composition containing ITO particles and a near-ultraviolet light absorbing organic compound. Patent Document 2 describes that this resin composition adjusts the wavelength dependency of the refractive index by improving the refractive index on the short wavelength side, and obtains a cured product that realizes a desired low refractive index and low Abbe number while increasing the transmittance in the near-infrared wavelength range by suppressing the blending amount of ITO particles. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2006-220689 A [Patent Document 2] International Publication No. 2020 / 171197 Summary of the Invention [Problem to be solved by the invention]

[0006] Conventionally, lenses using diffractive optical elements have been assumed to be applied to general cameras, and therefore research has been conducted to obtain low Abbe number diffractive optical elements that have a desired wavelength dependency of refractive index and high transmittance in the visible light wavelength range visible to the human eye, or in the near-infrared wavelength range from visible light to approximately 1.0 μm, as described in Patent Documents 1 and 2. Meanwhile, in various inspections such as electronic board inspection and solar cell inspection, shortwave infrared imaging technology using light in the shortwave infrared wavelength range of approximately 1.0 to 1.7 μm is used. Therefore, in order to obtain a chromatic aberration reduction effect in a wide wavelength range from visible light to the shortwave infrared wavelength range, the lenses used are also required to be diffractive optical elements having wavelength dependency of refractive index and high transmittance, which are desirable for low Abbe number diffractive optical elements. The present inventors have repeatedly studied a technique for applying a diffractive optical element that exhibits wavelength dependency of the refractive index by adding ITO particles to an optical system that uses light in the visible light to shortwave infrared wavelength range. As a result, it has been found that it is difficult to achieve high transmittance in the visible light to shortwave infrared wavelength range while maintaining the wavelength dependency of the refractive index by adding ITO particles with the technique described in Patent Document 1 or 2. In addition, it has been found that it is difficult to maintain the dispersion stability of the composition for a long period of time because the curable resin composition described in Patent Document 2 has low affinity between the near-ultraviolet light absorbing organic compound and the ITO particles. Therefore, a new technique is required that achieves high transmittance in the visible light to shortwave infrared wavelength range while maintaining the wavelength dependency of the refractive index by adding ITO particles without using a near-ultraviolet light absorbing organic compound.

[0007] The present invention aims to provide a curable resin composition containing ITO particles, in which a cured product obtained from the curable resin composition can exhibit high transmittance while maintaining a desired wavelength dependency of the refractive index over a range from visible light to short-wave infrared wavelengths. Another objective of the present invention is to provide a cured product obtained from the curable resin composition, and a diffractive optical element and a multilayer diffractive optical element containing the cured product. [Means for solving the problem]

[0008] The above problems were solved by the following means. [1] A curable resin composition comprising particles having a core-shell structure, the core of which is composed of indium tin oxide, a mono- or multi-functional (meth)acrylate compound, and a dispersant. [2] The curable resin composition according to [1], wherein the shell portion is composed of indium tin oxide or indium oxide. [3] The curable composition according to [1] or [2], wherein the tin concentration in the whole particles having a core-shell structure is 1.0 to 2.5 at %. [4] The curable resin composition according to any one of [1] to [3], wherein the absolute value of the difference between the tin concentration in the entire particle having the core-shell structure and the tin concentration in the shell portion is 0.5 at % or more. [5] The curable resin composition according to any one of [1] to [4], wherein the tin concentration in the core portion is 1.5 to 8.0 at %. [6] The curable resin composition according to any one of [1] to [5], wherein the shell portion has a tin concentration of 0 at % or more and less than 2.0 at %. [7] The curable resin composition according to any one of [1] to [6], wherein the shell portion has a thickness of 0.5 to 3.0 nm. [8] The curable resin composition according to any one of [1] to [7], wherein the content of the particles having a core-shell structure in the curable resin composition is 10 to 60 mass %. [9] The curable resin composition according to any one of [1] to [8], wherein the particle diameter of the particles having a core-shell structure is 15 to 50 nm.

[10] The curable resin composition according to any one of [1] to [9], which contains a photoradical polymerization initiator.

[11] A cured product of the curable resin composition according to any one of [1] to

[10] .

[12] A diffractive optical element comprising a surface having a diffraction grating pattern formed from the cured product according to

[11] .

[13] a first diffractive optical element and a second diffractive optical element; The first diffractive optical element is the diffractive optical element according to

[12] , A multi-layer diffractive optical element, in which a surface of the first diffractive optical element having a diffraction grating pattern and a surface of the second diffractive optical element having a diffraction grating pattern face each other.

[0009] In the present invention, the indication of compounds and substituents is used to include not only the compounds themselves and the substituents themselves, but also their salts and ions. For example, a carboxy group or the like may have an ionic structure with a hydrogen atom dissociated therefrom, or may have a salt structure. That is, in the present invention, the term "carboxy group" is used to include a carboxylate ion or a salt thereof. This also applies to other acidic groups. The monovalent or polyvalent cation in forming the above salt structure is not particularly limited, and examples thereof include inorganic cations and organic cations, and specifically, Na + , Li + and K + Alkali metal cations such as Mg 2+ , Ca 2+ and Ba 2+ and organic ammonium cations such as trialkylammonium cations and tetraalkylammonium cations. In the case of a salt structure, the type of salt may be one type or two or more types may be mixed, the salt type and the free acid structure group may be mixed in the compound, and further, a compound of a salt structure and a compound of a free acid structure may be mixed. In the present invention, when there are a plurality of substituents, linking groups, constitutional units, etc. (hereinafter referred to as substituents, etc.) represented by a specific symbol or formula, or when a plurality of substituents, etc. are specified at the same time, unless otherwise specified, each of the substituents, etc. may be the same or different from each other (regardless of the presence or absence of the expression "independently", each of the substituents, etc. may be the same or different from each other). This also applies to the definition of the number of the substituents, etc. In addition, when a plurality of substituents, etc. are adjacent to each other (especially when adjacent), they may be linked to each other to form a ring, unless otherwise specified. In addition, unless otherwise specified, a ring, for example, an alicyclic ring, an aromatic ring, or a heterocyclic ring may be further condensed to form a condensed ring. In the present invention, unless otherwise specified, when a double bond exists in a molecule in the form of an E or Z, the double bond may be either of them or a mixture thereof. In the present invention, unless otherwise specified, when a compound has one or more asymmetric carbons, the stereochemistry of such asymmetric carbons can be either the (R) or (S) form, independently of one another. As a result, the compound may be a mixture of stereoisomers, such as optical isomers or diastereoisomers, or may be a racemate. In the present invention, the description of the compounds includes those in which the structure is partially modified as long as the effect of the present invention is not impaired. Furthermore, compounds that are not specified as substituted or unsubstituted may have any substituent as long as the effect of the present invention is not impaired. In the present invention, the substituents (the same applies to linking groups and rings) that are not specified as substituted or unsubstituted mean that the group may have any substituent within the range that does not impair the desired effect, and the number of the substituents that may be had is not particularly limited. For example, when referring to an "alkyl group", it means that both an unsubstituted alkyl group and a substituted alkyl group are included. Similarly, when referring to an "aryl group", it means that both an unsubstituted aryl group and a substituted aryl group are included. In the present invention, when the number of carbon atoms of a certain group is specified, this carbon number means the total number of carbon atoms of the group unless otherwise specified in the present invention or this specification. In other words, when this group further has a substituent, it means the total number of carbon atoms including the substituent.

[0010] In the present invention, a numerical range expressed using "to" means a range including the numerical values ​​before and after "to" as the lower and upper limits. In the present invention, each of the components may be used alone or in combination of two or more. In the description of the content of each component in the curable resin composition of the present invention, when the curable resin composition contains a solvent, the content of each component is based on the component composition excluding the solvent from the curable resin composition. For example, when the curable resin composition is composed of 20 parts by mass of the solvent, 40 parts by mass of component A, and 40 parts by mass of component B, totaling 100 parts by mass, the content of component A in the composition is based on 80 parts by mass excluding the solvent, and is therefore 50% by mass.

[0011] In the present invention, "(meth)acrylate" refers to either or both of acrylate and methacrylate, and "(meth)acryloyl" refers to either or both of acryloyl and methacryloyl. The monomer in the present invention is distinguished from an oligomer and a polymer, and refers to a compound having a weight average molecular weight of 1000 or less.

[0012] In the present invention, the term "aliphatic hydrocarbon group" refers to a group obtained by removing any one hydrogen atom from a linear or branched alkane, a linear or branched alkene, or a linear or branched alkyne. In the present invention, the aliphatic hydrocarbon group is preferably an alkyl group obtained by removing any one hydrogen atom from a linear or branched alkane. Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, a 1-methylbutyl group, a 3-methylbutyl group, a hexyl group, a 1-methylpentyl group, a 4-methylpentyl group, a heptyl group, a 1-methylhexyl group, a 5-methylhexyl group, a 2-ethylhexyl group, an octyl group, a 1-methylheptyl group, a nonyl group, a 1-methyloctyl group, a decyl group, an undecyl group, a dodecyl group, a tridecyl group, a tetradecyl group, a pentadecyl group, a hexadecyl group, a heptadecyl group, an octadecyl group, a nonadecyl group, and an eicosyl group. In the present invention, the aliphatic hydrocarbon group (unsubstituted) is preferably an alkyl group having 1 to 20 carbon atoms, more preferably an alkyl group having 1 to 12 carbon atoms.

[0013] In the present invention, the term "alkyl group" refers to a straight-chain or branched alkyl group. Examples of the alkyl group include the above-mentioned examples. The same applies to the alkyl group in a group containing an alkyl group (an alkoxy group, an alkoxycarbonyl group, an acyl group, etc.). In the present invention, examples of the straight-chain alkylene group include, among the above-mentioned alkyl groups, groups obtained by removing one hydrogen atom bonded to the terminal carbon atom from a straight-chain alkyl group.

[0014] In the present invention, the alicyclic hydrocarbon ring refers to a saturated hydrocarbon ring (cycloalkane). Examples of the alicyclic hydrocarbon ring include cyclopropane, cyclobutane, cyclopentane, cyclohexane, cycloheptane, cyclooctane, cyclononane, and cyclodecane. In the present invention, the term "unsaturated hydrocarbon ring" refers to a hydrocarbon ring having a carbon-carbon unsaturated double bond that is not an aromatic ring. Examples of the unsaturated hydrocarbon ring include indene, indane, and fluorene.

[0015] In the present invention, the term "alicyclic hydrocarbon group" refers to a cycloalkyl group obtained by removing any one hydrogen atom from a cycloalkane. Examples of the alicyclic hydrocarbon group include a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, a cyclooctyl group, a cyclononyl group, and a cyclodecyl group, and a cycloalkyl group having 3 to 12 carbon atoms is preferred. In the present invention, the cycloalkylene group refers to a divalent group obtained by removing any two hydrogen atoms from a cycloalkane. An example of the cycloalkylene group is a cyclohexylene group.

[0016] In the present invention, the term "aromatic ring" means either or both of an aromatic hydrocarbon ring and an aromatic heterocyclic ring.

[0017] In the present invention, the aromatic hydrocarbon ring means an aromatic ring formed by carbon atoms alone. The aromatic hydrocarbon ring may be a single ring or a condensed ring. Examples of the aromatic hydrocarbon ring include benzene, biphenyl, biphenylene, naphthalene, anthracene, and phenanthrene. In the present invention, when the aromatic hydrocarbon ring is bonded to another ring, the aromatic hydrocarbon ring may be substituted on the other ring as a monovalent or divalent aromatic hydrocarbon group. In the present invention, the unsubstituted aromatic hydrocarbon ring is preferably an aromatic hydrocarbon ring having 6 to 14 carbon atoms.

[0018] In the present invention, when a monovalent group is referred to as an aromatic hydrocarbon group (also referred to as an aryl group), it means a monovalent group obtained by removing any one hydrogen atom from an aromatic hydrocarbon ring. Examples of the monovalent aromatic hydrocarbon group include a phenyl group, a biphenyl group, a 1-naphthyl group, a 2-naphthyl group, a 1-anthracenyl group, a 2-anthracenyl group, a 3-anthracenyl group, a 4-anthracenyl group, a 9-anthracenyl group, a 1-phenanthryl group, a 2-phenanthryl group, a 3-phenanthryl group, a 4-phenanthryl group, and a 9-phenanthryl group. Among these, a phenyl group, a 1-naphthyl group, and a 2-naphthyl group are preferred.

[0019] In the present invention, a divalent aromatic hydrocarbon group refers to a divalent group obtained by removing any two hydrogen atoms from an aromatic hydrocarbon ring. Examples of the divalent aromatic hydrocarbon group include divalent groups obtained by removing any one hydrogen atom from the above-mentioned monovalent aromatic hydrocarbon group. Among these, a phenylene group is preferred, and a 1,4-phenylene group is more preferred.

[0020] In the present invention, the aromatic heterocycle means an aromatic ring in which a ring is formed by at least one heteroatom and an atom selected from carbon atoms and heteroatoms. Examples of the heteroatom include an oxygen atom, a nitrogen atom, and a sulfur atom. The aromatic heterocycle may be a single ring or a condensed ring, and the number of atoms constituting the ring is preferably 5 to 20, more preferably 5 to 14. The number of heteroatoms in the atoms constituting the ring is not particularly limited, but is preferably 1 to 3, more preferably 1 to 2. Examples of aromatic heterocycles include a furan ring, a thiophene ring, a pyrrole ring, an imidazole, an isothiazole, an isoxazole, a pyridine, a pyrazine, a quinoline, a benzofuran, a benzothiazole, a benzoxazole, and examples of nitrogen-containing condensed aromatic rings described below. In the present invention, when an aromatic heterocycle is bonded to another ring, the aromatic heterocycle may be substituted on the other ring as a monovalent or divalent aromatic heterocyclic group.

[0021] In the present specification, when a monovalent group is referred to as an aromatic heterocyclic group (also referred to as a heteroaryl group), it means a monovalent group obtained by removing any one hydrogen atom from an aromatic heterocycle. Examples of monovalent aromatic heterocyclic groups include a furyl group, a thienyl group (preferably a 2-thienyl group), a pyrrolyl group, an imidazolyl group, an isothiazolyl group, an isoxazolyl group, a pyridyl group, a pyrazinyl group, a quinolyl group, a benzofuranyl group (preferably a 2-benzofuranyl group), a benzothiazolyl group (preferably a 2-benzothiazolyl group), and a benzoxazolyl group (preferably a 2-benzoxazolyl group). Among these, a furyl group, a thienyl group, a benzofuranyl group, a benzothiazolyl group, and a benzoxazolyl group are preferred, and a 2-furyl group and a 2-thienyl group are more preferred.

[0022] In the present invention, a divalent aromatic heterocyclic group refers to a divalent group obtained by removing two arbitrary hydrogen atoms from an aromatic heterocycle. Examples of the divalent aromatic heterocyclic group include a divalent group obtained by removing one arbitrary hydrogen atom from the above-mentioned monovalent aromatic heterocyclic group. In the present invention, examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. Effect of the Invention

[0023] The curable resin composition of the present invention is a curable resin composition containing ITO particles, and can give a cured product that exhibits high transmittance while maintaining the desired wavelength dependency of the refractive index over the visible light to short wave infrared wavelength range. Furthermore, the cured product of the present invention can exhibit high transmittance while maintaining the desired wavelength dependency of the refractive index over the visible light to short wave infrared wavelength range, and can be suitably used for diffractive optical elements and multilayer diffractive optical elements. [Brief description of the drawings]

[0024] [Figure 1]Fig. 1 is an example of a TOF-SIMS graph relating to the core-shell type ITO particles used in the present invention. In the graph of Fig. 1, the horizontal axis indicates depth, and the vertical axis indicates tin concentration. [Diagram 2] An example of a TOF-SIMS graph for uniformly doped ITO particles is shown in Figure 2. In the graph of Figure 2, the horizontal axis represents depth and the vertical axis represents tin concentration. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] <<Curable resin composition>> The curable resin composition of the present invention contains at least particles having a core-shell structure, the core of which is composed of indium tin oxide, a mono- or higher functional (meth)acrylate compound, and a dispersant. The curable resin composition of the present invention means a composition that has curability and can give a cured product (resin) by curing. The curable resin composition of the present invention may contain other components in addition to the above components. Each component will be described below.

[0026] <Core-shell type ITO tin particles> The curable resin composition of the present invention contains particles having a core-shell structure, the core of which is composed of indium tin oxide (ITO) (in the present invention, also referred to as "core-shell ITO particles"). By using such core-shell type ITO particles as the indium tin oxide particles contained in the curable resin composition, it is possible to obtain a cured product in which the decrease in transmittance in the shortwave infrared wavelength range (NIR) that occurs when particles in which the tin concentration of the ITO constituting the particles is uniform (hereinafter also referred to as "uniformly doped ITO particles") is added is suppressed, as described in Patent Document 1. This is because by making the ITO particles into a core-shell structure, it is possible to adjust the absorption to be sharper while maintaining the absorption wavelength shown by the uniformly doped ITO particles, thereby reducing the absorption in the tail of the absorption of the ITO particles in the NIR and improving the transmittance in the NIR.

[0027] (Core-shell structure) In the present invention, "particles having a core-shell structure, the core being made of ITO" means particles whose core is made of ITO and whose (i) shell is made of a compound different from ITO, or whose (ii) shell is made of ITO having a tin concentration different from the tin concentration of the core. The above (i) particles having a core made of ITO and a shell made of a compound different from ITO can be produced by using an ITO precursor solution to produce the core and a precursor solution of a compound different from ITO to produce the shell. The above (ii) particles having a core made of ITO and a shell made of ITO having a tin concentration different from that of the core can be produced by using precursor solutions having different tin concentrations to produce the shell and core.

[0028] When the shell portion is composed of a compound different from both indium oxide and ITO, it is possible to confirm that the particle has a core-shell structure by confirming that the shell portion has atoms other than oxygen atoms, indium atoms, and tin atoms and is composed of a compound different from ITO through a depth direction analysis of the particle by TOF-SIMS, which will be described later. For example, when the shell portion is composed of zinc oxide, it is possible to confirm that the maximum zinc concentration near the surface of the particle by the depth direction analysis of TOF-SIMS is 100 at%, and the zinc concentration in the depth range X is approximately 0 at%. On the other hand, when the shell portion is made of indium oxide or ITO, the particle diameter of the particles is measured by a TEM described later, and the tin concentration in the depth direction of the particles is measured by a TOF-SIMS described later, and confirmed by the following method. In a graph obtained by TOF-SIMS measurement, with the horizontal axis being the depth and the vertical axis being the tin concentration, the average tin concentration C in a depth range X that is equal to or greater than the depth corresponding to the radius of the particle and equal to or less than the depth corresponding to the diameter of the particle is determined. Sn X Aveand the minimum tin concentration near the particle surface, C Sn Surface Min When the absolute value of the difference between these values ​​satisfies the relationship of 1.0 at % or more, the particle is defined as having a core-shell structure for use in the present invention. In the present invention, the "particle radius" refers to a value obtained by multiplying the particle diameter measured by TEM by 0.5, and the "vicinity of the particle surface" refers to a depth range of 0 to 3.0 nm in depth direction analysis by TOF-SIMS. A detailed explanation will be given below using a concrete example. Figure 1 shows a graph obtained by TOF-SIMS measurement of core-shell type ITO particles with a particle diameter of 20 nm measured by TEM, which were prepared using an ITO precursor solution with a tin concentration of 4 at% for the shell and an indium oxide precursor solution with a tin concentration of 0 at% for the core. In Figure 1, the average tin concentration C in the depth range X from a depth of 10 nm, which corresponds to the radius of the particle, to a depth of 20 nm, which corresponds to the diameter of the particle, is Sn X Ave is 2.47 at%, and the minimum value of the tin concentration near the surface of the particle, C Sn Surface Min is 0.26 at %. The absolute value of this difference is 2.21 at %, which satisfies the requirement of 1.0 at % or more, and therefore the particles shown in Fig. 1 are core-shell type ITO particles used in the present invention. On the other hand, a graph obtained by TOF-SIMS measurement of uniformly doped ITO particles with a particle diameter of 20 nm measured by TEM, which were prepared using an ITO precursor solution with a tin concentration of 4 at%, is shown in Figure 2. As shown in Figure 2, in the case of uniformly doped ITO particles prepared using one type of ITO precursor solution, the C Sn X Ave is 2.66at%, and C Sn Surface Min The absolute value of the difference between them is 0.50 at %, and the difference is not 1.0 at % or more. In other words, the ITO particles are not of the core-shell type used in the present invention.

[0029] (Absolute value of the difference between the tin concentration in the whole particle and the tin concentration in the shell) The material constituting the shell of the core-shell type ITO particle is not particularly limited as long as it has the core-shell structure defined in the present invention and can obtain the effects of the present invention, and may be an organic compound or an inorganic compound. Among these, metal oxides containing one or more metal elements are preferred, and indium oxide or indium tin oxide are more preferred from the viewpoint of facilitating the production of core-shell type ITO particles whose core is composed of ITO. In the core-shell type ITO particles, the absolute value of the difference between the tin concentration of the whole particle and the tin concentration of the shell part is preferably 0.5 at% or more, and from the viewpoint of improving the transmittance, more preferably 1.0 at% or more. The upper limit of the absolute value of the difference between the tin concentration of the whole particle and the tin concentration of the shell part is preferably 20.0 at% or less, more preferably 8.0 at% or less, and even more preferably 4.0 at% or less. Note that, from the viewpoint of improving the transmittance, it is preferable that the tin concentration of the whole tin particle exceeds the tin concentration of the shell part. In the present invention, the tin concentration means the ratio (at%) of the number of tin atoms to the number of all metal atoms. The tin concentration of the core part and the tin concentration of the shell part mean the tin concentration of the metal atoms constituting the core part or the shell part, respectively. For example, when it is composed of ITO, it is the ratio of the number of tin atoms to the total number of indium atoms and tin atoms. The tin concentration in the shell portion is calculated from the particle size and tin concentration of the entire core-shell ITO particle, the thickness of the shell portion, and the particle size and tin concentration of the core portion, which are measured and calculated by the method described below.

[0030] (Tin concentration in the core, shell and whole particle) In the core-shell type ITO particles, it is preferable that the tin concentration in the core portion exceeds the tin concentration in the shell portion from the viewpoint of improving transmittance. The tin concentration in the core portion can be, for example, 2.0 to 20 at %, and from the viewpoint of further improving the transmittance, is more preferably 1.5 to 8.0 at %, further preferably 1.5 to 4.0 at %, and particularly preferably 1.5 to 3.5 at %. The tin concentration in the shell portion is preferably equal to or greater than 0 at % and less than 2.0 at %, more preferably 0 to 1.0 at %, and even more preferably 0 to 0.5 at %. The tin concentration in the entire core-shell ITO particle can be, for example, 0.5 to 3.0 at %, and from the viewpoint of further improving the transmittance, it is preferably 1.0 to 2.5 at %, and more preferably 1.0 to 2.0 at %. The tin concentration in the core portion and the tin concentration in the shell portion of the core-shell type ITO particles can be adjusted by adjusting the tin concentration in each precursor solution used to prepare the core-shell type ITO particles. The tin concentration in the entire particle can be adjusted by adjusting the tin concentration and thickness of the core and shell of the core-shell ITO particle.

[0031] (Particle size) The particle diameter of the core-shell type ITO particles can be, for example, 5 to 50 nm, and from the viewpoint of improving the transmittance, it is preferably 15 to 50 nm, more preferably 18 to 30 nm. By making it equal to or less than the above upper limit, it is possible to prevent deterioration of the transmittance due to Rayleigh scattering. In addition, when it is 5 nm or more, it is possible to manufacture the core-shell type ITO particles without technical difficulties. In particular, by making the particle diameter 15 nm or more (more preferably 18 nm or more), the composition is less likely to solidify when preparing the curable resin composition of the present invention, and the filling rate of the core-shell type ITO particles in the composition can be easily increased. In the present invention, it is particularly preferable to use core-shell type ITO particles having a particle diameter of 15 to 50 nm and a tin concentration in the core of 1.5 to 8.0 at %, from the viewpoint of further improving the transmittance.

[0032] (Shell thickness and core radius) In the core-shell type ITO particles, the ratio of the thickness of the shell part to the radius of the core part is not particularly limited as long as the effects of the present invention are achieved, but is, for example, preferably 0.10 to 0.50, more preferably 0.10 to 0.40, and even more preferably 0.15 to 0.35. The thickness of the shell portion in the core-shell type ITO particles can be, for example, 0.5 to 10.0 nm, and from the viewpoint of further improving the transmittance, it is preferably 0.5 to 3.0 nm, and more preferably 0.5 to 2.0 nm. The diameter of the core portion in the core-shell type ITO particle can be determined as the difference between the particle diameter of the core-shell type ITO particle determined by the method described below and the thickness of the shell portion.

[0033] The methods for measuring and calculating the tin concentration, particle diameter, or thickness of the core-shell type ITO particles are described below. Details of the measurement conditions are as described in the Examples below.

[0034] (ICP-MS analysis) The tin concentration in the entire core-shell ITO particle can be measured by ICP-MS (Inductively Coupled Plasma Mass Spectrometry). The tin concentration in the core can be measured by ICP-MS of the particles at the stage when the core is produced in the process of producing the core-shell type ITO particles. When the core-shell type ITO particles are used as the measurement sample, the tin concentration can be evaluated by performing composition analysis near the center of the particle using high-resolution TEM-EDX (Energy Dispersive X-ray Spectroscopy).

[0035] (Depth profile analysis by TOF-SIMS) The thickness of the shell of the core-shell ITO particle can be calculated by measuring the tin concentration in the depth direction by TOF-SIMS (Time of Flight-SIMS) and using the following method. The thickness of the shell part is the above C when viewed from 0 nm in the depth direction. Sn X Ave This means the depth at which the tin concentration first appears to be equal to the tin concentration obtained by multiplying 0.95 by C. Sn X Ave= 2.10 at %, and the depth Y at which the tin concentration first reaches 2.10 at % when viewed from 0 nm is 1.7 nm, and the thickness of the shell portion in this core-shell ITO particle is 1.7 nm.

[0036] (TEM analysis) The particle diameter of the core-shell type ITO particles can be calculated by averaging the equivalent circle diameters of the primary particles measured by a transmission electron microscope (TEM). That is, the particle area S of one particle in an electron microscope photograph taken by a TEM is measured, and the diameter of a perfect circle equivalent to this area S (equivalent circle diameter = 2(S / π) 0.5 In the present invention, the circle-equivalent diameters of 500 particles are randomly determined, and the average (arithmetic mean) of these 500 circle-equivalent diameters is calculated to be the particle diameter. The particle diameter of the core portion is determined as the value measured and calculated by TEM of the particles at the stage when the core portion is produced in the production process of the core-shell type ITO particles in the same manner as the particle diameter of the core-shell type ITO particles described above.

[0037] In addition, the tin concentration, particle diameter, or thickness of the core-shell type ITO particles in the cured product can be measured and calculated by ICP-MS, TOF-SIMS, or TEM as described above for particles obtained by dissolving the cured product using an alkaline solution or the like.

[0038] (Preparation of core-shell type ITO particles and composition) The curable resin composition of the present invention is preferably prepared by mixing the core-shell type ITO particles dispersed in a solvent with a dispersant and a (meth)acrylate compound described below. After mixing, the solvent used for dispersing the core-shell type ITO particles may or may not be removed from the curable resin composition by distillation or the like, but is preferably removed.

[0039] The core-shell type ITO particles can be made to have improved dispersibility in a solvent by being surface-modified. The surface modification of the core-shell type ITO particles is preferably performed using, for example, a monocarboxylic acid having 6 to 20 carbon atoms as a surface modification compound. The surface modification of the core-shell type ITO particles with the monocarboxylic acid can be performed by a conventional method, and is preferably performed by forming an ester bond between a carboxy group derived from the monocarboxylic acid and an oxygen atom on the surface of the core-shell type ITO particles, or by coordinating a carboxy group to an In or Ti atom. Examples of monocarboxylic acids having 6 to 20 carbon atoms include oleic acid (18 carbon atoms), stearic acid (18 carbon atoms), palmitic acid (16 carbon atoms), myristic acid (14 carbon atoms) and decanoic acid (10 carbon atoms), with oleic acid (18 carbon atoms) being preferred.

[0040] In the curable resin composition, the site derived from the surface modifying compound in the surface-modified core-shell type ITO particles (for example, a group derived from a monocarboxylic acid having 6 to 20 carbon atoms) may be directly bonded to the core-shell type ITO particles, or a part of the site may be replaced with a group derived from a dispersing agent described later, or the whole of the site may be replaced with a group derived from a dispersing agent described later. In the curable resin composition of the present invention, it is preferable that both the site derived from the surface modifying compound (for example, a group derived from a monocarboxylic acid having 6 to 20 carbon atoms) and the group derived from a dispersing agent described later are bonded to the surface of the core-shell type ITO particles.

[0041] The above solvents have a polarity component (δp) of the solubility parameter (SP value) of 0 to 6 MPa. 1 / 2 It is preferred that the solvent is The polar term component (δp) of the SP value is a value calculated by the Hansen solubility parameter. The Hansen solubility parameter is composed of intermolecular dispersion energy (δd), intermolecular polar energy (δp), and intermolecular hydrogen bonding energy (δh). In the present invention, the Hansen solubility parameter is calculated using HSPiP (version 4.1.07) software. Specifically, the solvent is preferably toluene (1.4), xylene (1.0) or hexane (0), and more preferably toluene. Note that the value in parentheses is the value of δp, and the unit is MPa. (1 / 2) It is.

[0042] The method for producing the core-shell type ITO particles is not particularly limited, but they can be produced, for example, according to the procedure described in ACS Nano 2016, 10, 6942-6951. A dispersion of the core-shell type ITO particles can be obtained by the procedure described in the same document, and the surface modification can also be performed by referring to the description in the same document. Specifically, a solution of a mixture of a monocarboxylic acid having 6 to 20 carbon atoms, an indium salt (e.g., indium acetate), and a tin salt (e.g., tin acetate) can be dropped into alcohol (a long-chain alcohol such as oleyl alcohol) heated to a high temperature, and the high temperature is maintained to form particles. The particles are then allowed to settle by adding a poor solvent (a lower alcohol such as ethanol) in which the polymer has low solubility, and the supernatant is then removed. The particles are then redispersed in a solvent such as toluene as described above to obtain a dispersion of surface-modified core-shell ITO particles.

[0043] The content of the core-shell type ITO particles in the curable resin composition of the present invention is preferably from 10 to 70 mass %, more preferably from 10 to 60 mass %, and further preferably from 20 to 50 mass %.

[0044] <Dispersant> The curable resin composition of the present invention contains a dispersant for dispersing the core-shell type ITO particles in the composition. As the dispersant, a cationic surfactant, an anionic surfactant, or an amphoteric surfactant can be used.

[0045] The cationic surfactant preferably has an amine salt type group or a quaternary ammonium salt type group. The anionic surfactant preferably has, as an acidic group, any one of a carboxy group, a phosphono group (-PO(OH)2), a phosphonooxy group (phosphate group, -OPO(OH)2), a hydrohydroxyphosphoryl group (-PH(O)(OH)), a sulfino group (-SO(OH)), a sulfo group (-SO2(OH)), and a sulfanyl group (-SH), or a salt of any one of them. The acidic group is more preferably any one of a carboxy group, a phosphono group, and a phosphonooxy group, or a salt of any one of them, and further preferably a carboxy group or a salt thereof. Examples of such anionic surfactants include carboxylic acid type surfactants such as (meth)acrylic acid compounds and hydroxystearic acid compounds, phosphoric acid type surfactants such as phosphoric acid compounds, sulfonic acid type surfactants such as amidosulfonic acid compounds, polycarboxylic acid type surfactants such as poly(meth)acrylic acid, and polyphosphoric acid type surfactants. The amphoteric surfactant includes an amino acid type or a betaine type amphoteric surfactant. The ionic groups such as acidic groups in the dispersant function as a dispersant by exhibiting an adsorption action to the surface of the core-shell type ITO particles through at least one of ionic bonds, covalent bonds, hydrogen bonds and coordinate bonds. Among these, the anionic surfactant is preferred as the dispersant.

[0046] Specific examples of the dispersant include DISPERBYK-106, 108, 110, 111, 118, 140, 142, 145, 161, 162, 163, 164, 167, 168, 180, 2013, 2055, and 2155 in the DISPERBYK series (trade name, manufactured by BYK Japan Co., Ltd.); and Hosmer M, Hosmer PE, Hosmer MH, and Hosmer PP in the Hosmer series (trade name, manufactured by Unichemical Co., Ltd.).

[0047] (acidic polymer) As the dispersant, an acidic polymer having the above-mentioned acidic group as an adsorption group that adsorbs to the core-shell type ITO particles (hereinafter, also referred to as an acidic polymer) is also preferably used. The acidic group of the acidic polymer is preferably a carboxy group or a salt thereof. The acidic polymer containing a carboxy group has a higher compatibility with the (meth)acrylate compound described below than, for example, a phosphoric acid-based dispersant having a phosphono group or a phosphonooxy group. Therefore, when the curable resin composition to which the acidic polymer having a carboxy group is added is cured, it is less likely to undergo phase separation or whitening. In addition, when forming a diffraction grating shape, the adhesion between the resin and the mold is good, and the curing shrinkage is small, so that the peeled surface is less likely to become rough. Furthermore, the viscosity is less likely to increase than, for example, an amine-based dispersant having an amine salt type group or a quaternary ammonium salt type group.

[0048] The acidic polymer preferably contains a (meth)acrylate polymer skeleton consisting of (meth)acrylate structural units. By containing a (meth)acrylate polymer skeleton, the compatibility between the acidic polymer and the (meth)acrylate compound in the curable resin composition can be improved. In addition, the refractive index of the cured product of the curable resin composition can be easily controlled. Examples of the (meth)acrylate structural unit include the structural units derived from (meth)acrylate monomers described in paragraph 0042 of JP-A-2012-107191, and a structural unit represented by the following general formula (P) is preferred.

[0049] [ka]

[0050] In the above formula, R P1 represents a hydrogen atom or a methyl group, R P2 indicates a monovalent substituent. * indicates a bond for incorporation into the polymer backbone. R P2 is preferably an alkyl group or an alicyclic hydrocarbon group, and more preferably an alkyl group. The alkyl group preferably has 1 to 20 carbon atoms, more preferably 1 to 12 carbon atoms, further preferably 1 to 8 carbon atoms, particularly preferably 1 to 4 carbon atoms, and most preferably 1 carbon atom. R P1 The methyl group and RP2 From the viewpoint of preventing an increase in viscosity of the curable resin composition, it is preferable that the alkyl group and the alicyclic hydrocarbon group which can be taken as the substituent do not contain the above-mentioned acidic group as a substituent.

[0051] The (meth)acrylate polymer skeleton may be linear or branched, and is preferably linear.

[0052] The number of (meth)acrylate structural units constituting one (meth)acrylate polymer skeleton is preferably 5-50, more preferably 8-40, and even more preferably 10-30.

[0053] The number of (meth)acrylate polymer skeletons contained in one molecule of the acidic polymer may be one or more, and for example, is preferably 1 to 6, and more preferably 1 to 4.

[0054] The acidic polymer preferably has a site containing an acidic group at at least one end of the (meth)acrylate polymer skeleton. "Having a site containing an acidic group at at least one end of the (meth)acrylate polymer skeleton" means having a site containing an acidic group directly or via a linking group at at least one end of the (meth)acrylate polymer skeleton. By having a site containing an acidic group at the end of the (meth)acrylate polymer skeleton, it is possible to prevent the viscosity increase of the curable resin composition caused by the acidic polymer. It is more preferable that the acidic polymer has a moiety containing the acidic group at an end of the polymer chain, and it is more preferable that the acidic polymer has a moiety containing an acidic group only on one end side of the (meth)acrylate polymer backbone. When one molecule of the acidic polymer contains two or more (meth)acrylate polymer skeletons, it is preferable that all of the (meth)acrylate polymer skeletons have a moiety containing an acidic group on at least one of the terminal sides of the (meth)acrylate polymer skeletons, and it is more preferable that all of the (meth)acrylate polymer skeletons have a moiety containing an acidic group on only one of the terminal sides of the (meth)acrylate polymer skeletons.

[0055] The acidic polymer more preferably contains an acidic group only in the (meth)acrylate polymer backbone, and further preferably the (meth)acrylate polymer backbone is linear and has a moiety containing an acidic group only at one end thereof, which can prevent an increase in viscosity of the curable resin composition.

[0056] The acidic polymer preferably has a structural portion represented by the following general formula (PA) as the structural portion containing the acidic group.

[0057] [ka]

[0058] In the above formula, A P represents an acidic group, LL represents a single bond or a linking group having a valence of x+1, and x is an integer of 1 to 10. * represents the bonding position with the remaining portion of the acidic polymer.

[0059] A P The acidic group which can be taken as the acidic polymer has the same meaning as the acidic group explained in the above-mentioned acidic polymer, and the preferred forms are also the same. Examples of the x+1-valent linking group that can be used as LL include an x+1-valent saturated fatty acid hydrocarbon group (a group obtained by removing x+1 hydrogen atoms from an alkane), an x+1-valent alicyclic hydrocarbon group (a group obtained by removing x+1 hydrogen atoms from an alicyclic hydrocarbon), and an x+1-valent group formed by combining these groups with a bond selected from -O-, -(C=O)-O-, and -(C=O)-NH-. The x+1 valent saturated fatty acid hydrocarbon group which can be taken as LL preferably has 1 to 10 carbon atoms, more preferably 1 to 7 carbon atoms, and even more preferably 1 to 5 carbon atoms. LL is preferably a x+1 valent saturated fatty acid hydrocarbon group or a group consisting of a combination of an x+1 valent saturated fatty acid hydrocarbon group and -O-. x is preferably an integer of 2 to 8, more preferably an integer of 2 to 4, and even more preferably an integer of 2.

[0060] The structure represented by the above general formula (PA) is preferably a structure represented by the following general formula (PA1), and from the viewpoint of improving the adsorption to the core-shell type ITO particles by having a carboxy group at a nearby site, a structure represented by the following formula (PA2) is more preferable.

[0061] [ka]

[0062] In the above formula, LL and x have the same meanings as LL and x in the above formula (PA). * indicates the bonding position to the remaining portion of the acidic polymer.

[0063] The number of structures represented by the above formula (PA), (PA1) or (PA2) contained in the acidic polymer is preferably 1 to 4.

[0064] The acid value of the acidic polymer is preferably 2.0 mgKOH / g or more and less than 100 mgKOH / g, and more preferably 2.0 mgKOH / g or more and less than 70 mgKOH / g. The acid value means the number of mg of potassium hydroxide required to neutralize the acidic components present in 1 g of the acidic polymer. By adjusting the molecular weight of the acidic polymer and the number of acidic groups such as carboxyl groups so that the acid value of the acidic polymer falls within the above-mentioned preferred range, it is possible to achieve both suitable viscosity and particle dispersion performance as a curable resin composition. By having an acid value of the acidic polymer of 2.0 mgKOH / g or more, the acidic polymer can be sufficiently adsorbed to and dispersed in the core-shell type ITO particles. In addition, by having an acid value of the acidic polymer of less than 100 mgKOH / g, it is possible to adjust the number and molecular size of the adsorptive groups and adjust the viscosity of the curable resin composition to a suitable range.

[0065] A preferred example of the acidic polymer is an acidic polymer having a structure represented by the following general formula (1). (R 1 -SL 2 ) n -L 1 -(L 3 -AR 2 ) m (1) In the above formula, R 1 represents -LL-(A P ) x and A represents a (meth)acrylate polymer skeleton represented by the above general formula (P). R 2 represents a substituent that does not contain a hydrogen atom or an acidic group, and L 1 represents a single bond or a (m+n)-valent linking group, L 2 and L 3 represents a single bond or a divalent linking group. m is an integer ranging from 1 to 8, and n is an integer ranging from 1 to 9, provided that m+n is 2 to 6.

[0066] R 1 Preferred examples of the alkyl group are alkyl groups substituted with a carboxy group, more preferred are alkyl groups having 1 to 10 carbon atoms substituted with 2 to 4 carboxy groups, still more preferred are alkyl groups having 1 to 7 carbon atoms substituted with 2 to 3 carboxy groups, and particularly preferred are alkyl groups having 1 to 5 carbon atoms substituted with two carboxy groups. Of these, the structure represented by the above formula (PA2) is preferred. R 2 is preferably a hydrogen atom. L 1 Examples of the (m+n)-valent linking group that can be taken as the linking group include a group formed by removing any (m+n) hydrogen atoms from a linear or branched alkane, and the following groups:

[0067] [ka]

[0068] L 2 and L 3 Examples of the divalent linking group that can be taken as the linking group include alkylene groups having 1 to 10 carbon atoms and alkylene groups having 1 to 10 carbon atoms in which any one or two or more non-adjacent -CH- groups are substituted with -O-, -S-, -C(=O)-, -OC(=O)-, -C(=O)O-, -OC(=O)O-, -NHC(=O)-, -C(=O)NH-, -OC(=O)NH-, -NHC(=O)O-, -SC(=O)- or -C(=O)S-.

[0069] The weight average molecular weight of the acidic polymer is preferably 1000 to 20000, more preferably 1000 to 15000, and even more preferably 1000 to 7000. By making it 1000 or more, it is possible to suppress the inclusion of bubbles that are generated during curing of the curable resin composition. In addition, by making it equal to or less than the above-mentioned preferable upper limit, even when an amount required for dispersing the core-shell type ITO particles is added to the curable resin composition, the flowability is not likely to decrease, and air is not likely to enter the steps of the mold and gaps are not likely to occur when forming the diffraction grating shape.

[0070] Specific examples of the acidic polymer include compounds having the following structure: In the following structural formula, one end of the (meth)acrylate polymer skeleton (R 2 ) is a hydrogen atom. m and n are the same as those in the above general formula (1).

[0071] [ka]

[0072] The polymer dispersant can be produced by a conventional method. For example, it can be produced by reacting a (meth)acrylate monomer with a compound that can terminate the polymerization reaction of the monomer and has an acidic group. Examples of such compounds include mercaptosuccinic acid, mercaptooxalic acid, and mercaptomalonic acid, and mercaptosuccinic acid is preferred. Furthermore, a polyol mercaptoalkylate or the like can be added and reacted to form a structure having a plurality of (meth)acrylate polymer skeletons in one molecule. In addition, for a polymer dispersant having a phosphonooxy group at one end, the method described in JP-A-6-20261 can be referred to.

[0073] In the curable resin composition, the content of the acidic polymer relative to 100 parts by mass of the core-shell type ITO particles is preferably 5 to 50 parts by mass, more preferably 5 to 30 parts by mass, further preferably 5 to 25 parts by mass, and particularly preferably 5 to 20 parts by mass. By setting the content ratio within the above preferred range, it is possible to stably disperse the core-shell type ITO particles in the curable resin composition while suppressing the inclusion of bubbles generated during curing.

[0074] [(Meth)acrylate compounds] The curable resin composition of the present invention contains a monofunctional or higher (meth)acrylate compound. The monofunctional or higher (meth)acrylate compound means a compound having one or more (meth)acryloyl groups as functional groups, and is also simply referred to as a "(meth)acrylate compound" in the present invention. The (meth)acrylate compound is not particularly limited in the number of functional groups as long as it has one or more functional groups, and may have, for example, up to eight functional groups. Specific examples of monofunctional or bifunctional (meth)acrylate compounds include, for example, Monomer 1 (phenoxyethyl acrylate), Monomer 2 (benzyl acrylate), Monomer 3 (tricyclodecane dimethanol diacrylate) and Monomer 4 (dicyclopentanyl acrylate). In addition, M-1 (1,6-hexanediol diacrylate), M-2 (1,6-hexanediol dimethacrylate), M-3 (benzyl acrylate), M-4 (isobornyl methacrylate), M-5 (dicyclopentanyl methacrylate), M-6 (dodecyl methacrylate), M-7 (2-ethylhexyl methacrylate), M-8 (2-hydroxyethyl acrylate), M-9 (hydroxypropyl acrylate) and M-10 (4-hydroxybutyl acrylate).

[0075] [ka]

[0076] [ka]

[0077] There is no particular limitation on the method for obtaining the (meth)acrylate compound, and the compound may be commercially obtained or synthesized by a conventional method. In the case of commercially available products, for example, Viscoat #192 PEA (monomer 1 above) (Osaka Organic Chemical Industry Co., Ltd.), Viscoat #160 BZA (monomer 2 above) (Osaka Organic Chemical Industry Co., Ltd.), Light Ester Bz (monomer 2 above) (Kyoeisha Chemical Co., Ltd.), A-DCP (monomer 3 above) (Shin-Nakamura Chemical Co., Ltd.), FA-513AS (monomer 4 above) (Hitachi Chemical Co., Ltd.), A-HD-N (M-1 above) (Shin-Nakamura Chemical Co., Ltd.), HD-N (M-2 above) (Shin-Nakamura Chemical Co., Ltd.), FA-BZA (M-3 above) (Hitachi Chemical Co., Ltd.), Light Ester IB-X (M-4 above) (manufactured by Kyoeisha Chemical Co., Ltd.), FA-513M (M-5 above) (manufactured by Hitachi Chemical Co., Ltd.), Light Ester L (M-6 above) (manufactured by Kyoeisha Chemical Co., Ltd.), 2EHA (M-7 above) (manufactured by Toagosei Co., Ltd.), HEA (M-8 above) (manufactured by Osaka Organic Chemical Industry Co., Ltd.), Light Ester HOP-A(N) (M-9 above) (manufactured by Kyoeisha Chemical Co., Ltd.), and 4-HBA (M-10 above) (manufactured by Osaka Organic Chemical Industry Co., Ltd.) can be preferably used.

[0078] In addition, when it is necessary to increase the surface hardness or abrasion resistance of the cured product, the curable resin composition preferably contains a polyfunctional (meth)acrylate compound having three or more (meth)acryloyl groups in the molecule. By containing a polyfunctional (meth)acrylate compound having three or more (meth)acryloyl groups in the molecule, the crosslink density of the cured product can be effectively improved, so that the surface hardness and abrasion resistance can be increased while maintaining a high partial dispersion ratio. The upper limit of the number of (meth)acryloyl groups in the polyfunctional (meth)acrylate compound having three or more (meth)acryloyl groups in the molecule is not particularly limited, but is preferably 8 or less, more preferably 6. When commercially available, for example, A-TMPT (monomer 5), A-TMMT (monomer 6), AD-TMP (monomer 7), and A-DPH (monomer 8) (manufactured by Shin-Nakamura Chemical Co., Ltd.) can be preferably used.

[0079] [ka]

[0080] In addition to the above, examples of the (meth)acrylate monomers include those described in paragraphs 0037 to 0046 of JP-A-2012-107191. The molecular weight of the (meth)acrylate compound is preferably 100-500.

[0081] The content of the (meth)acrylate compound in the curable resin composition of the present invention is preferably 1 to 50 mass%, more preferably 2 to 40 mass%, and further preferably 3 to 30 mass%. By adjusting the amount of the (meth)acrylate compound in the curable resin composition, the function of the cured product to relieve stress during thermal changes can be adjusted.

[0082] In particular, when it is necessary to increase the surface hardness or abrasion resistance of the cured product, the curable resin composition preferably contains 5 to 50 mass %, more preferably 10 to 45 mass %, and even more preferably 25 to 40 mass % of a polyfunctional (meth)acrylate compound having three or more (meth)acryloyl groups in the molecule, based on the total mass of the curable resin composition (solid mass excluding the solvent when a solvent is contained).

[0083] <Other ingredients> The curable resin composition of the present invention may further contain other components in addition to the core-shell type ITO particles, the dispersant, and the (meth)acrylate compound. Specific examples of other components include the following polymerization initiators. In addition, the composition may contain the polymer described in paragraphs

[0099] to

[0108] of International Publication No. 2020 / 171197.

[0084] [Polymerization initiator] The curable resin composition of the present invention preferably contains, as the polymerization initiator, at least one selected from a thermal radical polymerization initiator and a photoradical polymerization initiator.

[0085] (Thermal radical polymerization initiator) The curable resin composition of the present invention preferably contains a thermal radical polymerization initiator. By the action of this thermal radical polymerization initiator, the curable resin composition can be thermally polymerized to form a cured product having high heat resistance.

[0086] As the thermal radical polymerization initiator, a compound that is usually used as a thermal radical polymerization initiator can be appropriately used according to the conditions of the thermal polymerization (thermal curing) step described later. For example, organic peroxides can be mentioned, and specifically, the following compounds can be used. Examples of the peroxyalkylene compounds include 1,1-di(t-hexylperoxy)cyclohexane, 1,1-di(t-butylperoxy)cyclohexane, 2,2-di(4,4-di-(t-butylperoxy)cyclohexyl)propane, t-hexylperoxyisopropyl monocarbonate, t-butylperoxy-3,5,5-trimethylhexanoate, t-butylperoxylaurate, dicumyl peroxide, di-t-butyl peroxide, t-butylperoxy-2-ethylhexanoate, t-hexylperoxy-2-ethylhexanoate, cumene hydroperoxide, t-butyl hydroperoxide, t-butylperoxy-2-ethylhexyl, and 2,3-dimethyl-2,3-diphenylbutane.

[0087] When a thermal radical polymerization initiator is contained, the content of the thermal radical polymerization initiator in the curable resin composition of the present invention is preferably 0.01 to 10 mass %, more preferably 0.05 to 5.0 mass %, and even more preferably 0.05 to 2.0 mass %.

[0088] (Photoradical polymerization initiator) The curable resin composition of the present invention preferably contains a photoradical polymerization initiator. As the photoradical polymerization initiator, a compound that is usually used as a photoradical polymerization initiator can be appropriately used according to the conditions of the photopolymerization (photocuring) step described later, and specifically, the following compounds can be used. For example, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, bis(2,6-dimethylbenzoyl)-2,4,4-trimethylpentylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,4,4-trimethylpentylphosphine oxide, bis(2,6-dichlorobenzoyl)-2,4,4-trimethylpentylphosphine oxide, 1-phenyl-2-hydroxy-2-methylpropan-1-one, 1-hydroxycyclohexyl phenyl ketone, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-1-one, 1,2-diphenylethanedione, methylphenyl glyoxylate, 1 -[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one, 2,2-dimethoxy-1,2-diphenylethan-1-one, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, and the like can be mentioned.

[0089] Among them, in the present invention, as the photoradical polymerization initiator, 1-hydroxycyclohexyl phenyl ketone (e.g., Irgacure 184 (trade name) manufactured by BASF), bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (e.g., Irgacure 819 (trade name) manufactured by BASF), 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide (e.g., Irgacure TPO (trade name) manufactured by BASF), 2,2-dimethoxy-1,2-diphenylethan-1-one (e.g., Irgacure 651 (trade name) manufactured by BASF), 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one can be preferably used.

[0090] When a photoradical polymerization initiator is contained, the content of the photoradical polymerization initiator in the curable resin composition of the present invention is preferably 0.01 to 5.0 mass%, more preferably 0.05 to 1.0 mass%, and even more preferably 0.05 to 0.5 mass%. It is preferable that the curable resin composition contains both a photoradical polymerization initiator and a thermal radical polymerization initiator. In this case, the total content of the photoradical polymerization initiator and the thermal radical polymerization initiator in the curable resin composition is preferably 0.01 to 5 mass%, more preferably 0.05 to 1.0 mass%, and even more preferably 0.05 to 0.5 mass%.

[0091] (Other additives, etc.) As long as the effects of the present invention are achieved, the curable resin composition of the present invention may contain additives such as polymers or monomers other than the above-mentioned components, dispersants, plasticizers, heat stabilizers, and release agents.

[0092] <Other properties of the curable resin composition> The viscosity of the curable resin composition of the present invention is preferably 5000 mPa·s or less, more preferably 3000 mPa·s or less, even more preferably 2500 mPa·s or less, and particularly preferably 2000 mPa·s or less. By setting the viscosity of the curable resin composition within the above range, the handleability when molding the cured product can be improved, and a high-quality cured product can be formed. The viscosity of the curable resin composition is preferably 50 mPa·s or more, more preferably 100 mPa·s or more, even more preferably 200 mPa·s or more, and particularly preferably 500 mPa·s or more.

[0093] <Uses of the curable resin composition> The use of the curable resin composition of the present invention is not particularly limited, but it is preferably used as a material for producing a diffractive optical element. In particular, it is used as a material for producing a diffractive optical element having a low refractive index and a low Abbe number in a multi-layer type diffractive optical element, and can provide excellent diffraction efficiency.

[0094] <<Cured product>> The cured product of the present invention is formed from the curable resin composition of the present invention. The cured product is obtained by polymerizing a polymerizable compound such as a (meth)acrylate compound, but the cured product of the present invention may contain unreacted monomers. The cured product obtained by curing the curable resin composition of the present invention is transparent over the visible light to short wave infrared wavelength range (approximately 600 to 1600 nm), and has low refractive indices at wavelengths of 656.27 nm and 1550 nm, as described below. For example, when the cured product is formed into a sheet having a thickness of 6 μm, the transmittance at a wavelength of 656.27 nm can be 90% or more, and the transmittance at a wavelength of 1550 nm can be 40% or more, preferably 45% or more, and more preferably 50% or more. Here, the transmittance means a value measured using a spectrophotometer (for example, the spectrophotometer "V-670" manufactured by JASCO Corporation).

[0095] The refractive index at a wavelength of 656.27 nm of the cured product obtained by curing the curable resin composition of the present invention is preferably 1.45 to 1.60, and more preferably 1.50 to 1.55. The refractive index at a wavelength of 1550 nm of the cured product obtained by curing the curable resin composition of the present invention is preferably from 1.35 to 1.55, and more preferably from 1.40 to 1.50.

[0096] The birefringence Δn at a wavelength of 587 nm of the cured product of the curable resin composition of the present invention (also referred to as birefringence Δn(587 nm) in the present invention) is preferably 0.00≦Δn≦0.01. The birefringence Δn(587 nm) is more preferably 0.001 or less, and even more preferably less than 0.001. The lower limit of the birefringence Δn(587 nm) may be 0.00001 or 0.0001.

[0097] The birefringence Δn (587 nm) of the cured product can be determined by the following method: A film-like sample is prepared, and the birefringence within a circle with a diameter of 10 mm including the center of the sample is measured using a birefringence evaluation device (for example, product name: WPA-100, manufactured by Photonic Lattice Co., Ltd.), and the birefringence Δn (587 nm) can be obtained by calculating the average value of the birefringence at a wavelength of 587 nm.

[0098] <Method of manufacturing the cured product> The cured product of the present invention can be produced by photocuring the curable resin composition of the present invention by irradiation with light or thermally curing the composition by heating. In the case of photocuring, it is preferable to include the above-mentioned photoradical polymerization initiator in the curable resin composition, and in the case of thermal curing, it is preferable to include the above-mentioned thermal radical polymerization initiator in the curable resin composition. Regarding the conditions for photocuring, the description of the light irradiation for the diffractive optical element described below can be preferably applied. In the thermal curing, the heating temperature can be, for example, 150° C. or higher, preferably 160 to 270° C., more preferably 165 to 250° C., and even more preferably 170 to 230° C. During heating, pressure may be applied simultaneously. The pressure during pressure application is preferably 0.098 MPa to 9.8 MPa, more preferably 0.294 MPa to 4.9 MPa, and even more preferably 0.294 MPa to 2.94 MPa. The time for thermal curing is preferably 30 to 1000 seconds, more preferably 30 to 500 seconds, and further preferably 60 to 300 seconds. The atmosphere during thermal curing (thermal polymerization) is preferably air or an inert gas-substituted atmosphere, and more preferably an atmosphere substituted with nitrogen until the oxygen concentration becomes 1% or less.

[0099] <<Diffractive optical elements>> The diffractive optical element of the present invention is a diffractive optical element that includes a surface having a diffraction grating pattern formed from the cured product of the present invention, and is formed by curing the curable resin composition of the present invention. The diffractive optical element of the present invention preferably has a maximum thickness of 2 μm to 100 μm. The maximum thickness is more preferably 2 μm to 50 μm, and particularly preferably 2 μm to 30 μm. The step (grating thickness) of the diffraction grating shape (periodic structure) of the diffractive optical element is preferably 1 μm to 100 μm, and more preferably 1 μm to 50 μm. Furthermore, the pitch of the diffraction grating shape of the diffractive optical element may be between 0.1 mm to 10 mm, and preferably varies within the same diffractive optical element depending on the required optical aberration.

[0100] The diffractive optical element can be manufactured, for example, by the following procedure. The curable resin composition is sandwiched between the surface of a mold having a surface processed into a diffraction grating shape and a transparent substrate. After this, the curable resin composition may be pressurized and stretched to a desired range. In the sandwiched state, light is irradiated from the transparent substrate side to cure the curable resin composition. Then, the cured product is released from the mold. After release, light may be irradiated from the opposite side to the transparent substrate side.

[0101] Examples of the transparent substrate include flat glass and flat transparent resin (such as (meth)acrylic resin, polycarbonate resin, and polyethylene terephthalate). The transparent substrate used in the above production may be included in the diffractive optical element as it is, or may be peeled off.

[0102] The surface of the mold that has been machined into the diffraction grating shape is preferably treated with chromium nitride, which provides good mold releasability and increases the efficiency of manufacturing diffractive optical elements. An example of the chromium nitride treatment is a method for forming a chromium nitride film on the surface of a mold. Methods for forming a chromium nitride film on the surface of a mold include, for example, CVD (Chemical Vapor Deposition) and PVD (Physical Vapor Deposition). The CVD method is a method for forming a chromium nitride film on the surface of a substrate by reacting a raw material gas containing chromium with a raw material gas containing nitrogen at high temperature. The PVD method is a method for forming a chromium nitride film on the surface of a substrate by utilizing an arc discharge (arc type vacuum deposition method). This arc type vacuum deposition method is a method in which a cathode (evaporation source) made of, for example, chromium is placed in a vacuum vessel, an arc discharge is caused between the cathode and the wall surface of the vacuum vessel via a trigger, the cathode is evaporated, and at the same time, the metal is ionized by the arc plasma, a negative voltage is applied to the substrate, and a reactive gas (for example, nitrogen gas) is introduced into the vacuum vessel at a pressure of about several tens of mTorr (1.33 Pa), whereby the ionized metal and the reactive gas react with each other on the surface of the substrate to form a compound film.

[0103] The light used for the light irradiation to cure the curable resin composition is preferably ultraviolet light or visible light, more preferably ultraviolet light. For example, a metal halide lamp, a low pressure mercury lamp, a high pressure mercury lamp, an ultra-high pressure mercury lamp, a germicidal lamp, a xenon lamp, an LED (Light Emitting Diode) light source lamp, etc. are preferably used. The illuminance of the ultraviolet light used for the light irradiation to cure the curable resin composition is 1 to 100 mW / cm. 2is preferably 1 to 75 mW / cm 2 More preferably, the intensity is 5 to 50 mW / cm 2 It is more preferable that the ultraviolet light has a different illuminance. The ultraviolet light may be irradiated multiple times. The exposure dose of the ultraviolet light is 0.4 to 10 J / cm. 2 is preferably 0.5 to 5 J / cm 2 More preferably, it is 1 to 3 J / cm 2 The atmosphere during light irradiation is preferably air or an inert gas-substituted atmosphere, and more preferably an atmosphere in which air has been substituted with nitrogen until the oxygen concentration becomes 1% or less.

[0104] <<Multilayer diffractive optical element>> The multi-layer diffractive optical element of the present invention includes a first diffractive optical element and a second diffractive optical element, the first diffractive optical element being a diffractive optical element formed from the cured product of the present invention, and a surface having a diffraction grating shape in the first diffractive optical element and a surface having a diffraction grating shape in the second diffractive optical element being opposed to each other. It is preferable that the surfaces having the diffraction grating shape are in contact with each other. It is preferable to use a diffractive optical element formed by curing the curable resin composition of the present invention as a first diffractive optical element, and to further stack a second diffractive optical element formed of a different material so that their lattice-shaped surfaces face each other to form a multi-layer diffractive optical element. In this case, it is preferable that the lattice-shaped surfaces are in contact with each other. By forming the second diffractive optical element from a material with a higher refractive index and higher Abbe number than the first diffractive optical element, the occurrence of flare and the like can be suppressed, and the chromatic aberration reducing effect of the multi-layer diffractive optical element can be fully utilized.

[0105] The refractive index of the second diffractive optical element at a wavelength of 656.27 nm is preferably 1.55 to 1.70, and more preferably 1.56 to 1.65. The refractive index of the second diffractive optical element at a wavelength of 656.27 nm is greater than the refractive index of the first diffractive optical element used simultaneously in the multi-layer diffractive optical element, that is, the refractive index of the second diffractive optical element at a wavelength of 656.27 nm > the refractive index of the first diffractive optical element at a wavelength of 656.27 nm is satisfied. The refractive index of the second diffractive optical element at a wavelength of 1550 nm is preferably 1.55 to 1.70, and more preferably 1.56 to 1.65. The refractive index of the second diffractive optical element at a wavelength of 1550 nm is greater than the refractive index of the first diffractive optical element used simultaneously in the multi-layer diffractive optical element, that is, the refractive index of the second diffractive optical element at a wavelength of 1550 nm > the refractive index of the first diffractive optical element at a wavelength of 1550 nm is satisfied.

[0106] The material for forming the second diffractive optical element is not particularly limited as long as it can provide a cured product with a high refractive index and a high Abbe number. For example, a curable resin composition containing a sulfur atom, a halogen atom, or a (meth)acrylate monomer having an aromatic ring structure, or a curable resin composition containing zirconium oxide and a (meth)acrylate monomer can be used.

[0107] The multi-layer diffractive optical element can be manufactured, for example, by the following procedure. A material for forming a second diffractive optical element is sandwiched between the diffraction grating-shaped surface (surface obtained after the above-mentioned demolding) of the diffractive optical element formed by curing the curable resin composition of the present invention and the transparent substrate. After this, the material may be pressurized and stretched to a desired range. In the sandwiched state, light is irradiated from the transparent substrate side to cure the material. Then, the cured product is released from the mold. That is, the multi-layer diffractive optical element of the present invention preferably comprises a first diffractive optical element, a second diffractive optical element and a transparent substrate arranged in this order.

[0108] Examples of the transparent substrate include the same transparent substrate as that used in producing the diffractive optical element (first diffractive optical element). The transparent substrate used in the above production may be included in the multi-layer diffractive optical element as it is, or may be peeled off.

[0109] It is preferable that the diffraction efficiency of the multi-layered diffractive optical element is high. For example, the diffraction efficiency of the multi-layered diffractive optical element for the first-order light at a wavelength of 656.27 nm is preferably 50% or more, more preferably 80% or more, even more preferably 85% or more, and particularly preferably 95% or more. In addition, the diffraction efficiency of the multi-layered diffractive optical element for the first-order light at a wavelength of 1550 nm is preferably 90% or more, more preferably 95% or more. Since the multi-layer diffractive optical element exhibits high diffraction efficiency for first-order light at the above-mentioned wavelengths of 656.27 nm and 1550 nm, unnecessary diffracted light can be sufficiently suppressed, and a high-performance lens can be realized.

[0110] The multilayer diffractive optical element preferably has a maximum thickness of 50 μm to 20 mm, more preferably 50 μm to 10 mm, and particularly preferably 50 μm to 3 mm.

[0111] <Lens> The diffractive optical element and the multi-layer diffractive optical element of the present invention can each be used as a lens. A film or member can be provided on the surface or periphery of the lens depending on the environment and application of the lens. For example, a protective film, an anti-reflection film, a hard coat film, etc. can be formed on the surface of the lens. In addition, a composite lens can be formed by laminating the lens on a glass lens or a plastic lens. Furthermore, the periphery of the lens can be fitted into a substrate holding frame or the like to fix it. However, these films, frames, etc. are members added to the lens and are distinguished from the lens itself as referred to in this specification.

[0112] The lens is preferably used as an image pickup lens for mobile phones, digital cameras, etc., a film taking lens for televisions, video cameras, etc., and further as an in-vehicle lens. EXAMPLES

[0113] The present invention will be described in more detail below based on examples. The materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following examples can be changed as appropriate without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the specific examples shown below. In the present invention, "room temperature" means 25°C.

[0114] [Synthesis example] The ITO particles and the dispersant were synthesized as follows.

[0115] [1. Synthesis of ITO particles] (1) Synthesis of core-shell type ITO particles (ITO-01) First, 300 ml of oleic acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), 42.475 g of indium acetate (manufactured by Kojundo Chemical Co., Ltd.), and 1.60 g of tin (IV) acetate (manufactured by Alfa Aesar) were placed in a flask and heated at 160°C for 1 hour in a nitrogen flow environment to obtain a yellow, transparent precursor solution with a tin concentration of 3.0 at%. In addition, 300 ml of oleic acid and 43.79 g of indium acetate were placed in a separate flask and heated at 160° C. for 1 hour in a nitrogen flow environment, to obtain a yellow, transparent precursor solution with a tin concentration of 0 at %. Each of the prepared precursor liquids was filled into a gas-tight syringe.

[0116] Next, 65 ml of oleyl alcohol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added to another flask and heated in a nitrogen flow at 285° C. 40 ml of the precursor solution with a tin concentration of 3.0 at % filled in the gas-tight syringe was dropped into the heated solvent at a rate of 1.75 ml / min using a syringe pump. After the dripping of the precursor solution with a tin concentration of 3.0 at% was completed, the solution was held for 5 minutes, and then 70 ml of the precursor solution with a tin concentration of 0 at% was dripped at a rate of 1.75 ml / min using a syringe pump. After the dripping of the precursor solution with a tin concentration of 0 at% was completed, heating was stopped and the sample was cooled to room temperature.

[0117] The obtained reaction liquid was centrifuged, the supernatant was removed, and the mixture was redispersed in toluene. The series of steps of adding ethanol, centrifuging, removing the supernatant, and redispersing in toluene was repeated three times to obtain 75 ml of a toluene dispersion of oleic acid-coordinated core-shell type ITO particles (ITO-01). The solid content of the dispersion of ITO particles (ITO-01) was 6 mass %, and the proportion of the surface modifying component (oleic acid) in this solid content was 6 mass %. Hereinafter, the solids concentration and the ratio of the surface modification component in the solids of the dispersions of ITO nanoparticles (ITO-02) to (ITO-07) are the same as those of the dispersion of ITO nanoparticles (ITO-01). (Solid content concentration evaluation method) 10 ml of the obtained dispersion of ITO particles was sampled and heated at 200° C. for 30 minutes in a glass dish on a hot plate, and the solid content was calculated from the mass of the residue after heating and the mass of the dispersion before heating.

[0118] (2) Synthesis of uniformly doped ITO particles (ITO-02) First, 300 ml of oleic acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), 42.475 g of indium acetate (manufactured by Kojundo Chemical Co., Ltd.), and 1.60 g of tin (IV) acetate (manufactured by Alfa Aesar) were placed in a flask and heated at 160°C for 1 hour in a nitrogen flow environment to obtain a yellow, transparent precursor solution with a tin concentration of 3.0 at%. Each of the prepared precursor liquids was filled into a gas-tight syringe.

[0119] Next, 65 ml of oleyl alcohol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added to another flask and heated in a nitrogen flow at 285° C. 110 ml of the precursor solution with a tin concentration of 3.0 at % filled in the gas-tight syringe was dropped into the heated solvent at a rate of 1.75 ml / min using a syringe pump. After the dropping of the precursor solution was completed, the heating was stopped and the material was cooled to room temperature.

[0120] The reaction solution obtained was centrifuged, the supernatant was removed, and the solution was redispersed in toluene. The series of steps of adding ethanol, centrifuging, removing the supernatant, and redispersing in toluene was repeated three times to obtain 75 ml of a toluene dispersion of uniformly doped ITO particles (ITO-02) coordinated with oleic acid.

[0121] (3) Synthesis of core-shell type ITO particles (ITO-03) A precursor solution with a tin concentration of 3.0 at % and a precursor solution with a tin concentration of 0 at %, which were used in the preparation of the core-shell type ITO nanoparticles (ITO-01), were each filled in advance into a gas-tight syringe. 65 ml of oleyl alcohol was added to the flask, and the mixture was heated to 285° C. in a nitrogen flow. 20 ml of the precursor solution with a tin concentration of 3.0 at % filled in the gas-tight syringe was dripped into the heated solvent at a rate of 1.75 ml / min using a syringe pump. After dripping of the precursor solution with a tin concentration of 3.0 at % was completed, 20 ml of the precursor solution with a tin concentration of 0 at % was further dripped at a rate of 1.75 ml / min using a syringe pump. After dripping of the precursor solution with a tin concentration of 0 at % was completed, heating was stopped and the mixture was cooled to room temperature. The obtained reaction liquid was centrifuged, the supernatant was removed, and the mixture was redispersed in toluene. The series of steps of adding ethanol, centrifuging, removing the supernatant, and redispersing in toluene was repeated three times to obtain 37.5 ml of a toluene dispersion of oleic acid-coordinated core-shell type ITO particles (ITO-03).

[0122] (4) Synthesis of core-shell type ITO particles (ITO-04) A precursor solution with a tin concentration of 2.5 at% and a precursor solution with a tin concentration of 0.5 at% were previously filled into gas-tight syringes, which had been prepared in the same manner as the precursor solution used to produce the core-shell type ITO nanoparticles (ITO-01), except that the ratio of indium acetate and tin acetate was changed. 65 ml of oleyl alcohol was added to the flask, and the mixture was heated to 285° C. in a nitrogen flow. 40 ml of the precursor solution with a tin concentration of 2.5 at % filled in the gas-tight syringe was dripped into the heated solvent at a rate of 1.75 ml / min using a syringe pump. After dripping of the precursor solution with a tin concentration of 2.5 at % was completed, 70 ml of the precursor solution with a tin concentration of 0.5 at % was further dripped at a rate of 1.75 ml / min using a syringe pump. After dripping of the precursor solution with a tin concentration of 0.5 at % was completed, heating was stopped and the mixture was cooled to room temperature. The obtained reaction liquid was centrifuged, the supernatant was removed, and the mixture was redispersed in toluene. The series of steps of adding ethanol, centrifuging, removing the supernatant, and redispersing in toluene was repeated three times to obtain 75 ml of a toluene dispersion of oleic acid-coordinated core-shell type ITO particles (ITO-04).

[0123] (5) Synthesis of core-shell type ITO particles (ITO-05) A precursor solution with a tin concentration of 6.0 at% was prepared in the same manner as in the preparation of the precursor solution used to produce the core-shell type ITO nanoparticles (ITO-01) except that the ratio of indium acetate and tin acetate was changed, and a precursor solution with a tin concentration of 0% was also prepared in a gas-tight syringe. 65 ml of oleyl alcohol was added to the flask, and the mixture was heated to 285° C. in a nitrogen flow. 20 ml of the precursor solution with a tin concentration of 6.0 at % filled in the gas-tight syringe was dripped into the heated solvent at a rate of 1.75 ml / min using a syringe pump. After dripping of the precursor solution with a tin concentration of 6.0 at % was completed, 90 ml of the precursor solution with a tin concentration of 0 at % was further dripped at a rate of 1.75 ml / min using a syringe pump. After dripping of the precursor solution with a tin concentration of 0 at % was completed, heating was stopped and the mixture was cooled to room temperature. The obtained reaction liquid was centrifuged, the supernatant was removed, and the mixture was redispersed in toluene. The series of steps of adding ethanol, centrifuging, removing the supernatant, and redispersing in toluene was repeated three times to obtain 75 ml of a toluene dispersion of oleic acid-coordinated core-shell type ITO particles (ITO-05).

[0124] (6) Synthesis of core-shell type ITO particles (ITO-06) A precursor solution with a tin concentration of 10.0 at% was prepared in the same manner as in the preparation of the precursor solution used to produce the core-shell type ITO nanoparticles (ITO-01) except that the ratio of indium acetate and tin acetate was changed, and a precursor solution with a tin concentration of 0 at% was also prepared in a gas-tight syringe. 65 ml of oleyl alcohol was added to the flask, and the mixture was heated to 285° C. in a nitrogen flow. 12 ml of the precursor solution with a tin concentration of 10.0 at % filled in the gas-tight syringe was dripped into the heated solvent at a rate of 1.75 ml / min using a syringe pump. After dripping of the precursor solution with a tin concentration of 10.0 at % was completed, 98 ml of the precursor solution with a tin concentration of 0 at % was further dripped at a rate of 1.75 ml / min using a syringe pump. After dripping of the precursor solution with a tin concentration of 0 at % was completed, heating was stopped and the mixture was cooled to room temperature. The obtained reaction liquid was centrifuged, the supernatant was removed, and the mixture was redispersed in toluene. The series of steps of adding ethanol, centrifuging, removing the supernatant, and redispersing in toluene was repeated three times to obtain 75 ml of a toluene dispersion of oleic acid-coordinated core-shell type ITO particles (ITO-06).

[0125] (7) Synthesis of core-shell type ITO particles (ITO-07) A precursor solution with a tin concentration of 4.0 at% was prepared in the same manner as in the preparation of the precursor solution used to produce the core-shell type ITO nanoparticles (ITO-01) except that the ratio of indium acetate and tin acetate was changed, and the precursor solution with a tin concentration of 0% was also prepared in a gas-tight syringe. 65 ml of oleyl alcohol was added to the flask, and the mixture was heated to 275° C. in a nitrogen flow. 25 ml of the precursor solution with a tin concentration of 4.0 at % filled in the gas-tight syringe was dripped into the heated solvent at a rate of 1.75 ml / min using a syringe pump. After dripping of the precursor solution with a tin concentration of 4.0 at % was completed, 85 ml of the precursor solution with a tin concentration of 0 at % was further dripped at a rate of 1.75 ml / min using a syringe pump. After dripping of the precursor solution with a tin concentration of 0 at % was completed, heating was stopped and the mixture was cooled to room temperature. The obtained reaction liquid was centrifuged, the supernatant was removed, and the mixture was redispersed in toluene. The series of steps of adding ethanol, centrifuging, removing the supernatant, and redispersing in toluene was repeated three times to obtain 75 ml of a toluene dispersion of oleic acid-coordinated core-shell type ITO particles (ITO-07).

[0126] (8) Synthesis of core-shell type ITO particles (ITO-08) A precursor solution with a tin concentration of 2.0 at% was prepared in the same manner as in the preparation of the precursor solution used to produce the core-shell type ITO nanoparticles (ITO-01) except that the ratio of indium acetate and tin acetate was changed, and the precursor solution with a tin concentration of 0% was also prepared in a gas-tight syringe. 65 ml of oleyl alcohol was added to the flask, and the mixture was heated to 285° C. in a nitrogen flow. 20 ml of the precursor solution with a tin concentration of 2.0 at % filled in the gas-tight syringe was dripped into the heated solvent at a rate of 1.75 ml / min using a syringe pump. After dripping of the precursor solution with a tin concentration of 2.0 at % was completed, 90 ml of the precursor solution with a tin concentration of 0 at % was further dripped at a rate of 1.75 ml / min using a syringe pump. After dripping of the precursor solution with a tin concentration of 0 at % was completed, heating was stopped and the mixture was cooled to room temperature. The obtained reaction liquid was centrifuged, the supernatant was removed, and the mixture was redispersed in toluene. The series of steps of adding ethanol, centrifuging, removing the supernatant, and redispersing in toluene was repeated three times to obtain 75 ml of a toluene dispersion of oleic acid-coordinated core-shell type ITO particles (ITO-08).

[0127] (9) Synthesis of core-shell type ITO particles (ITO-09) A precursor solution with a tin concentration of 10.0 at% was prepared in the same manner as in the preparation of the precursor solution used to produce the core-shell type ITO nanoparticles (ITO-01) except that the ratio of indium acetate and tin acetate was changed, and a precursor solution with a tin concentration of 0% was also prepared in a gas-tight syringe. 65 ml of oleyl alcohol was added to the flask, and the mixture was heated to 285° C. in a nitrogen flow. 7.2 ml of the precursor solution with a tin concentration of 10.0 at % filled in the gas-tight syringe was dripped into the heated solvent at a rate of 1.75 ml / min using a syringe pump. After dripping of the precursor solution with a tin concentration of 10.0 at % was completed, 40.8 ml of the precursor solution with a tin concentration of 0 at % was further dripped at a rate of 1.75 ml / min using a syringe pump. After dripping of the precursor solution with a tin concentration of 0 at % was completed, heating was stopped and the mixture was cooled to room temperature. The obtained reaction liquid was centrifuged, the supernatant was removed, and the mixture was redispersed in toluene. The series of steps of adding ethanol, centrifuging, removing the supernatant, and redispersing in toluene was repeated three times to obtain 40 ml of a toluene dispersion of oleic acid-coordinated core-shell type ITO particles (ITO-09).

[0128] As a result of the depth direction analysis by TOF-SIMS described later, it was found that the above-mentioned core-shell type ITO particles (ITO-01) and (ITO-03) to (ITO-09) all had the above-mentioned C Sn X Ave and C. Sn Surface Min The absolute value of the difference between the above and the uniformly doped ITO particles (ITO-02) satisfies the relationship of 1.0 at % or more. Sn X Ave and C. Sn Surface MinThe absolute value of the difference from was less than 1.0 at %.

[0129] For each of the ITO particles prepared above, ICP-MS analysis, depth direction analysis by TOF-SIMS, and TEM analysis were performed. In addition, ICP-MS analysis and TEM analysis were performed for the particles at the stage where the core part was prepared in the production process of the core-shell type ITO particles. Based on these measurement results, the particle diameter, shell thickness, and tin concentration of the core part, shell part, and whole particle were obtained. These are summarized in Table 1. The tin concentration in the shell portion was calculated from the particle size and tin concentration of the entire core-shell ITO particle, the thickness of the shell portion, and the particle size and tin concentration of the core portion.

[0130] [Measurement A: TEM analysis] The particle diameter of the ITO particles and the particle diameter of the core portion were calculated using a TEM JFM-ARM300F2 GRAND (product name, manufactured by JEOL Ltd.) based on the above-mentioned method for measuring the particle diameter of ITO particles. [Measurement B: Depth profile analysis by TOF-SIMS] The thickness of the shell of the core-shell type ITO particle was calculated by performing a tin concentration analysis in the depth direction using TOF.SIMS5 (product name, manufactured by ION-TOF) as a TOF-SIMS, as described above. In the TOF-SIMS measurement, the ITO particle dispersion was dropped onto aluminum foil using a pipette and dried to obtain a measurement sample, and the measurement was performed within the measurement sample, which is a film-like structure made up of accumulated ITO particles. In addition, the horizontal axis in the depth direction analysis was converted from time to depth using the sputtering rate calculated by TOF-SIMS measurement using a sputtered ITO film (transmittance 84% at a wavelength of 550 nm, surface resistivity 13.2 Ω / sq) as a standard sample. [Measurement C: ICP-MS analysis] The tin concentration in the whole particle and the tin concentration in the core portion were measured using an Agilent 8900 triple quadrupole (product name, manufactured by Agilent Technologies) as the ICP-MS. Regarding the tin concentration of the uniformly doped ITO particles, the tin concentration of the entire particle was also measured by the above method.

[0131] 2. Synthesis of Dispersant (1) Synthesis of dispersant (A-1) 24.0 g of methyl methacrylate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) and 1.80 g of mercaptosuccinic acid (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) were dissolved in 28 mL of methyl ethyl ketone and heated to 70° C. under a nitrogen stream. A solution of 0.24 g of a polymerization initiator (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd., V-65) dissolved in 12 mL of methyl ethyl ketone was added dropwise to this solution over 30 minutes. After the dropwise addition was completed, the reaction was allowed to proceed for another 4.5 hours at 70° C. After cooling, the reaction solution was added dropwise to a mixture of 200 mL of cooled water and 600 mL of methanol, and the precipitated powder was filtered and dried to obtain 15 g of the following dispersant (A-1). This polymer dispersant (A-1) is essentially composed of a polymer having a carboxyl group at one end. The weight average molecular weight of the obtained polymer was 5900 as converted into standard polystyrene by GPC (Gel Permeation Chromatography), and the dispersity (Mw / Mn) was 1.70. The acid value was calculated by measuring the number of mg of potassium hydroxide required to neutralize the free fatty acid present in 1 g of the obtained polymer, and was found to be 24 mgKOH / g.

[0132] [ka]

[0133] [Example] The toluene dispersions of ITO particles (ITO-01) to (ITO-09) were previously diluted with toluene to a solid content concentration of 4.75% by mass, and each curable resin composition was prepared as follows. 1. Preparation of Curable Resin Compositions 1-1 to 1-11 0.54 g of dispersant (A-1) and 2.0 g of 1,6-hexanediol dimethacrylate (HDDMA, manufactured by Tokyo Chemical Industry Co., Ltd.) were added to 51.6 g of the toluene dispersion of ITO particles (ITO-01) prepared above, and dissolved. The toluene was distilled off by vacuum suction while heating in a water bath at about 70°C. 0.01 g of IRGACURE 819 (trade name, manufactured by BASF, photopolymerization initiator) was added to the mixture obtained after distillation and dissolved to prepare a curable resin composition 1-1. Curable resin compositions 1-2 to 1-11 were prepared in the same manner as in the preparation of the above curable resin composition 1-1 so as to have the compositional ratios shown in the following table.

[0134] 2. Preparation of Curable Resin Composition 2 19.2 g of FA-512AS (trade name, dicyclopentenyloxyethyl acrylate, Hitachi Chemical Co., Ltd.) and 1.1 g of A9300-1CL (trade name, Shin-Nakamura Chemical Co., Ltd.) were added to 55.5 g of a zirconium oxide dispersion (trade name: SZR-K, Sakai Chemical Industry Co., Ltd.) and stirred until homogenous. Methanol and MEK (methyl ethyl ketone) were distilled off by vacuum suction while heating in a water bath at about 70°C. 0.40 g of IRGACURE 651 (trade name, BASF, photopolymerization initiator) was added to the mixture obtained after distillation and dissolved to prepare a curable resin composition 2.

[0135] 3. Preparation of Cured Products of Curable Resin Compositions 1-1 to 1-11 The curable resin composition 1-1 was sandwiched between hydrophobically treated glass plates, and was then exposed to a UV irradiation device (product name: EXECURE 3000, manufactured by HOYA CANDEO OPTRONICS) with an integrated light dose of 1.0 J / cm. 2 , illuminance 30mW / cm 2 After irradiating with UV (ultraviolet rays) under the conditions, the integrated light quantity was 1.0 J / cm 2 , illuminance 5mW / cm 2 A cured product was produced by irradiating the coating with UV light under the following conditions: The thickness of the cured product thus obtained was 6 μm. Cured products of curable resin compositions 1-2 to 1-11 were prepared in the same manner as in preparation of a cured product of curable resin composition 1-1, except that curable resin composition 1-1 was replaced with curable resin composition 1-2 to 1-11.

[0136] [4. Preparation of cured product of curable resin composition 2] The curable resin composition 2 was sandwiched between hydrophobically treated glass plates, and was then irradiated with a UV irradiation device (product name: EXECURE3000, manufactured by HOYA CANDEO OPTRONICS) with an integrated light dose of 2.0 J / cm. 2 , illuminance 5mW / cm 2 The cured product was irradiated with UV light under the following conditions to produce a cured product. The film thickness of the cured product obtained as described above was 6 μm.

[0137] [Evaluation 1: Transmittance measurement] The cured products of the curable resin compositions 1-1 to 1-11 prepared under the above conditions were measured for transmittance at wavelengths of 400 to 1800 nm using a spectrophotometer (product name: V-670, manufactured by JASCO Corporation), and the transmittance %T at 656.27 nm was 656 and transmittance at 1550 nm %T 1550 Based on the above, the transmittance of the cured product was evaluated according to the following evaluation criteria. A rating of "B-" or higher is practical, and a rating of "A" or higher is preferable. The results are shown in Table 1. - Evaluation Criteria - A :%T 656 is 90% or more, and %T 1550 More than 50% B+:%T 656 is 90% or more, and %T 1550 Between 45% and 50% B-:%T 656 is 90% or more, and %T 1550 Between 40% and 45% C :%T 656 is 90% or more, and %T 1550 Between 30% and 40% D :%T 656 is 90% or more, and %T 1550 Less than 30% E :%T 656is less than 90% and %T 1550 Less than 30%

[0138] [Evaluation 2: Evaluation of refractive index] The refractive indexes of each of the cured products of Curable Resin Compositions 1-1 to 1-11 and the cured product of Curable Resin Composition 2 at wavelengths of 656.27 nm and 1550 nm were measured using a multi-wavelength Abbe refractometer DR-M2 (trade name, manufactured by Atago Co., Ltd.). The cured products of each of the curable resin compositions 1-1 to 1-11 had a refractive index nC of 1.45 to 1.60 at a wavelength of 656.27 nm, and a refractive index of 1.35 to 1.55 at a wavelength of 1550 nm. The cured product of the curable resin composition 2 had a refractive index nC of 1.599 at a wavelength of 656.27 nm and a refractive index of 1.587 at a wavelength of 1550 nm.

[0139] [Evaluation 3: Evaluation of the diffraction efficiency of multi-layer diffractive optical elements] In the diffractive optical element shown in FIG. 2 of JP2008-241734A, a cured product of any one of the above-mentioned curable resin compositions 1-1 to 1-11 was used as a first diffraction grating, a cured product of the above-mentioned curable resin composition 2 was used as a second diffraction grating, and the common grating thickness of the first and second diffraction gratings was set to 9.6 μm. The diffraction efficiency of the multilayer diffractive optical element was evaluated. The diffraction efficiency was evaluated by calculating the diffraction efficiency of the first-order light at wavelengths of 656.27 nm and 1550 nm using the refractive index and grating thickness values ​​measured in Evaluation 2 above, using formulas 23 and 24 in JP 2008-241734 A, and evaluating the diffraction efficiency of the multi-layer diffractive optical element according to the following evaluation criteria. A rating of "B" or higher is considered to be good. The results are shown in Table 1. - Evaluation Criteria - A: The diffraction efficiency at a wavelength of 656.27 nm was 95% or more, and the diffraction efficiency at a wavelength of 1550 nm was 95% or more. B: The diffraction efficiency at a wavelength of 656.27 nm was 85% or more and less than 95%, and the diffraction efficiency at a wavelength of 1550 nm was 95% or more. C: The diffraction efficiency at a wavelength of 656.27 nm was 85% or more and less than 95%, and the diffraction efficiency at a wavelength of 1550 nm was less than 95%. D: The diffraction efficiency at a wavelength of 656.27 nm was less than 85%, and the diffraction efficiency at a wavelength of 1550 nm was less than 95%.

[0140] [Table 1]

[0141] [Table 1-2]

[0142] The components in the table are as follows. (ITO particles) ITO-01 to ITO-9: ITO particles (ITO-01) to (ITO-9) prepared above (Dispersant) A-1: Dispersant (A-1) prepared above Hosmer PP: Product name, manufactured by Unichemical Co., Ltd. BYK-111: DISPERBYK-111 (trade name), polyester polyether copolymer having phosphoric acid groups, manufactured by BYK ((Meth)acrylate Compounds) HDDMA: 1,6-Hexanediol dimethacrylate (Photopolymerization initiator) Irgacure 819: Product name, manufactured by BASF

[0143] [ka]

[0144] The blending amount is expressed in mass % (also referred to as wt%), and the blending amount of ITO particles is expressed as a solid content amount. The units of the tin concentration in the core portion and the tin concentration in the shell portion are both at %, and the units of the particle diameter of the ITO particles and the thickness of the shell portion are both nm.

[0145] The results in Table 1 reveal the following: The cured product obtained from comparative curable resin composition 1-2 containing uniformly doped ITO particles had a low transmittance of less than 30% at 1550 nm, and was unable to achieve high transmittance while maintaining the desired wavelength dependency of the refractive index over the visible to short-wave infrared wavelength range. In contrast, the cured product obtained from any one of the curable resin compositions 1-1 and 1-3 to 1-11 of the present invention, which contain the core-shell type ITO particles, a monofunctional or higher (meth)acrylate compound, and a dispersant, can achieve high transmittance while maintaining the desired wavelength dependency of the refractive index over the visible light to short wave infrared wavelength range, and was superior in transmittance in the short wave infrared wavelength range compared to the case of using uniformly doped ITO particles. [Explanation of symbols]

[0146] X: Range from the depth equivalent to the radius of the particle to the depth equivalent to the diameter of the particle Y When viewed from 0 nm in the depth direction, 0.95×C Sn X Ave This is the first depth to show the same tin concentration as that of

Claims

1. A curable resin composition comprising particles having a core-shell structure, the core being composed of indium tin oxide and the shell being composed of indium tin oxide or indium oxide, a mono- or higher functional (meth)acrylate compound, and a dispersant.

2. 2. The curable composition according to claim 1, wherein the tin concentration in the whole particles having the core-shell structure is 1.0 to 2.5 at %.

3. 3. The curable resin composition according to claim 1, wherein an absolute value of a difference between a tin concentration in the entire particle having a core-shell structure and a tin concentration in the shell portion is 0.5 at % or more.

4. The curable resin composition according to any one of claims 1 to 3, wherein the tin concentration in the core portion is 1.5 to 8.0 at%.

5. The curable resin composition according to any one of claims 1 to 4, wherein the tin concentration in the shell portion is 0 at% or more and less than 2.0 at%.

6. The curable resin composition according to any one of claims 1 to 5, wherein the shell portion has a thickness of 0.5 to 3.0 nm.

7. The curable resin composition according to any one of claims 1 to 6, wherein the content of the particles having a core-shell structure in the curable resin composition is 10 to 60 mass%.

8. The curable resin composition according to any one of claims 1 to 7, wherein the particle diameter of the particles having a core-shell structure is 15 to 50 nm.

9. The curable resin composition according to any one of claims 1 to 8, further comprising a photoradical polymerization initiator.

10. A cured product of the curable resin composition according to any one of claims 1 to 9.

11. A diffractive optical element comprising a surface having a diffraction grating pattern formed from the cured product according to claim 10.

12. a first diffractive optical element and a second diffractive optical element; The first diffractive optical element is the diffractive optical element according to claim 11 , A multi-layer diffractive optical element, wherein a surface of the first diffractive optical element having a diffraction grating pattern and a surface of the second diffractive optical element having a diffraction grating pattern face each other.

Citation Information

Patent Citations

  • Ultraviolet-curing resin composition and heat-ray-shielding film made therefrom

    JP1998218917A

  • Interlayer for laminated glass and laminated glass

    JP2006001809A

  • Liquid curable composition and its cured film

    JP2006348069A

  • Transparent base material with heat ray shielding film, coating material for forming heat ray shielding film and method of manufacturing transparent base material with heat ray shielding film

    JP2009072985A

  • Photochromic laminate

    JP2017042981A